A STUDY ON CUSTOMER PERCEPTION AND CURRENT PRACTICE OF EBANKING TECHNOLOGY IN CHENNAI CITY - K. , Ananthasuresh; A , Devendran; S V , Elumalaiyan (International Journal of Psychosocial Rehabilitation, 2020)
Now a days Internet banking or Virtual banking is one of the emerging trends in the world. The development progress in the IT have brought about a lot of changes in Banking Industry, it has been in the form of E-Banking or Internet Banking, which is now replacing the traditional banking mechanism. E-Banking is one of the gift to human beings by computer technology. It is a fast spreading service that allows customers to use computer to access account transactions from a remote location such as at home or at the workplace convenience to customers. Telephone Banking, Mobile Banking, Electronic Fund Transfer, ATM and Internet Banking are some of the E-Banking products. An attempt is made in this paper to determine the customer’s perception toward the E-Banking services particularly in Chennai City. The main objective of the study is to find out the customer perception and satisfaction towards E-Banking. The study was done based on interview schedule with a sample of 250 respondents. The data ware analyzed using simple percentage analysis and chisquare test to find customer perception and satisfaction towards E-Banking.